A cyanine dye based supramolecular photosensitizer enabling visible-light-driven organic reaction in water. Issue 85 (8th October 2021) - Shigemitsu, Hajime; Tamemoto, Tomoe; Ohkubo, Kei; Mori, Tadashi; Osakada, Yasuko; Fujitsuka, Mamoru; Kida, Toshiyuki
Abstract : Photooxidation of hydrophobic aromatic compounds in water was successfully performed by a supramolecular photosensitizer composed of an amphiphilic cyanine dye. Abstract : We report the aggregation-induced photosensitizing activity of a cyanine dye in water and the mechanism. In addition, using the supramolecular assembly, visible-light-driven photooxidation of hydrophobic aromatic compounds in water was successfully performed.